PENINGKATAN KOMPETENSI BAHASA INGGRIS MELALUI ENGLISH FOR SPECIFIC PURPOSES UNTUK MENDUKUNG ILMU PROMOSI KESEHATAN DALAM PERSIAPAN DUNIA KERJA BAGI MAHASISWA KESEHATAN MASYARAKAT INSTITUT KESEHATAN MEDISTRA LUBUK PAKAM - GINTING, SULASTRI BR; Tinambunan, Tedty Rohaya; Silalahi, Novrika (INSTITUT KESEHATAN DELI HUSADA, 2025)
English language competence has become a crucial skill in various professional fields, particularly in health sciences. In the era of globalization, health workers are not only required to possess technical expertise but also the ability to communicate effectively in English, especially in the context of health promotion. This community service program aimed to enhance the English proficiency of public health students through the implementation of English for Specific Purposes (ESP) to prepare them for workforce readiness. The program was conducted at the Faculty of Public Health, Medistra Health Institute, Lubuk Pakam, on July 7–8, 2025, and involved 120 students. The activities consisted of pre-tests, interactive workshops, practical training, and post-tests. Workshop sessions included the introduction of health promotion terminology, reading and interpreting health-related texts, developing promotional materials such as leaflets and posters in English, and practicing oral communication through role plays and presentations. The results showed a significant improvement, with an average score increase of 96.67% between the pre-test and post-test. Participants demonstrated better mastery of health promotion vocabulary, reading comprehension, writing skills, and oral communication in English. Furthermore, they produced tangible outputs such as digital leaflets, health posters, and short educational videos. Based on participant feedback, 92.6% expressed high satisfaction with the program, indicating its relevance and benefits. This initiative has successfully equipped students with applicable English skills that integrate health science knowledge and support their preparedness for the global workforce. Continuous and expanded ESP programs are recommended to further strengthen students’ competitiveness and professional readiness. Kemampuan berbahasa Inggris telah menjadi keterampilan penting dalam berbagai bidang profesi, khususnya di bidang kesehatan. Di era globalisasi, tenaga kesehatan tidak hanya dituntut memiliki kompetensi teknis, tetapi juga keterampilan berkomunikasi dalam bahasa Inggris, terutama dalam konteks promosi kesehatan. Program pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kompetensi bahasa Inggris mahasiswa kesehatan masyarakat melalui pendekatan English for Specific Purposes (ESP) guna mempersiapkan mereka menghadapi dunia kerja. Kegiatan dilaksanakan di Fakultas Kesehatan Masyarakat, Institut Kesehatan Medistra Lubuk Pakam pada tanggal 7–8 Juli 2025 dengan jumlah peserta sebanyak 120 mahasiswa. Rangkaian kegiatan meliputi pre-test, workshop interaktif, pelatihan praktik, dan post-test. Materi yang diberikan mencakup pengenalan terminologi promosi kesehatan, membaca dan memahami teks kesehatan, penulisan materi promosi kesehatan seperti leaflet dan poster dalam bahasa Inggris, serta latihan komunikasi lisan melalui role play dan presentasi. Hasil kegiatan menunjukkan